2011
DOI: 10.1111/j.1743-6109.2011.02422.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Erectile Dysfunction: A Review of the Interface between Sex and Molecular Biomarkers

Abstract: Introduction In recent years, new tools for the study of molecular biology and genetics have resulted in significant contributions to the scientific community. The potential use of genetic variations as biomarkers in the management of current and future conditions is generating considerable excitement in health care for disorders such as erectile dysfunction (ED). Aim This review briefly describes the molecular and genetic me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 83 publications
0
6
0
1
Order By: Relevance
“…The pathophysiology of ED in diabetic men includes vascular and neurogenic causes, oxidative processes, endothelial dysfunction, and changes in the nitric oxide (NO) system (Phé & Rouprêt, ). However, recent candidate gene association studies suggest that human genetic variations could represent a potential supplementary risk factor in the pathogenesis of ED (Andersen et al ., ; Lopushnyan & Chitaley, ). Several epidemiological studies have been performed to identify candidate genes associated with ED (Andersen et al ., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathophysiology of ED in diabetic men includes vascular and neurogenic causes, oxidative processes, endothelial dysfunction, and changes in the nitric oxide (NO) system (Phé & Rouprêt, ). However, recent candidate gene association studies suggest that human genetic variations could represent a potential supplementary risk factor in the pathogenesis of ED (Andersen et al ., ; Lopushnyan & Chitaley, ). Several epidemiological studies have been performed to identify candidate genes associated with ED (Andersen et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent candidate gene association studies suggest that human genetic variations could represent a potential supplementary risk factor in the pathogenesis of ED (Andersen et al ., ; Lopushnyan & Chitaley, ). Several epidemiological studies have been performed to identify candidate genes associated with ED (Andersen et al ., ). Polymorphisms of endothelial nitric oxide synthase ( eNOS ) and guanine nucleotide‐binding proteins ( GNB3 ) genes were associated with increased ED risk in diverse ethnic groups (Wang et al ., ; Safarinejad et al ., ; Gao et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Erectile dysfunction is a common clinical entity that affects mainly men older than 40 years according to the classical causes of erectile dysfunction, such as diabetes mellitus, hypertension, and several common lifestyle factors [ 1 ]. There are various causes for organic erectile dysfunction (ED), most of which involve damage to nerves, blood vessels, corporal smooth muscle, and/or endothelial cells [ 2 , 3 ]. The incidence of ED among men suffering diabetes mellitus (DM) is three times higher than in non-diabetic men.…”
Section: Introductionmentioning
confidence: 99%
“…For the past few decades, research has increased our understanding of the neuroscience underlying SD. The pursuit of genomic regions that confer risk for SD has been the focus of many investigations [6]. Using the study by Santtila et al.…”
Section: Introductionmentioning
confidence: 99%
“…For the past few decades, research has increased our understanding of the neuroscience underlying SD. The pursuit of genomic regions that confer risk for SD has been the focus of many investigations [6]. Using the study by Santtila et al [7] as an example, the authors showed that the dopamine transporter gene polymorphism is associated with premature ejaculation (PE).…”
Section: Introductionmentioning
confidence: 99%